Analisis Framing Berita Perempuan Bakar Diri Dalam Media Online Detik.Com Dan Kompas.Com - Yana, Melinda Defy; Setiawan, Hendra (Jurnal Ilmiah Wahana Pendidikan, 2023)
The method used in this research is descriptive qualitative method. The results of the study show that there are differences in framing by Detik.com and Kompas.com media, especially in syntactic, thematic and rhetorical elements. In the syntactical aspect, the Detik.com media writes news using serenity where the title of the news is framing using a choice of words that lead to the news content and involve the police in the title which makes people curious about the news. Meanwhile, at Kompas.com, when writing the title, it is interesting with the use of the word "reckless" and makes people curious about the news. In the thematic elements in Detik.com and Kompas.com media there is no use of pronouns to mention sources in source quotations. The thematic elements in the Detik.com media include explanatory and causal coherence in the writing of the news. Meanwhile, on Kompas.com media there is a hyphen using a comma hyphen "," and cause and effect in writing the news. And the rhetorical element in Detik.com media uses a choice of words that are quite easy to understand by the general public regarding the case of the woman who self-immolated. Meanwhile, Kompas.com uses a choice of words that are quite difficult for the general public to understand regarding the case of women self-immolation and the use of words that attract the attention of readers. Also accompanied by pictures that support the content of the news delivered.